From Lead To Performance: How Leadership Motivation And Discipline Shape Employee Productivity In PT. Tjiwi Kimia, Tbk. - Nur Kholifah; Teguh Widodo (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objectives: This study examines the influence of leadership style, work motivation, and work discipline on the productivity of employees at PT Tjiwi Kimia Tbk as a representative of large manufacturing industries in Indonesia. The objective is to understand the extent to which these organizational behavior factors affect performance in the context of industrial efficiency and competition. Background Problems: There has been a decline in employee discipline and productivity at PT Tjiwi Kimia Tbk during the 2023–2025 period. This study seeks to answer the extent to which leadership style, work motivation, and work discipline influence productivity simultaneously and partially. Novelty: The novelty of this research lies in the empirical analysis of the relationship between leadership, motivation, and discipline in the context of the manufacturing industry in Indonesia, which has rarely been studied simultaneously. Most studies have focused on the public and education sectors, thus failing to describe the characteristics of industries with high production pressure. Research Methods: This study uses an associative quantitative approach with multiple linear regression. Primary data was obtained through a Likert scale questionnaire from 70 employees in three main departments (HR, Mill Service, and Export-Import), then analyzed using SPSS version 27 through validity and reliability tests, classical assumption tests, and hypothesis tests (F and t tests). Finding/Results: The results show that leadership, motivation, and work discipline simultaneously have a significant effect on productivity (F = 24.335; Sig. < 0.001). Partially, only work motivation has a positive and significant effect (Sig. = 0.006), while the other two variables do not have a significant effect. Conclusion: Work motivation is a dominant factor in increasing employee productivity. These results reinforce Maslow’s 1943 theory and Robbins and Judge’s 2013 theory regarding the importance of motivational needs in a work environment that supports self-actualization. Companies are advised to strengthen policies regarding rewards and career development, as well as create a work environment that supports sustainable productivity.